Forensic age estimation based on magnetic resonance imaging of third molars: converting 2D staging into 3D staging - Jannick De Tobel; Elke Hillewig; Koenraad Verstraete (Taylor & Francis Group, 2017)
Background: Established methods to stage development of third molars for forensic age estimation are based on the evaluation of radiographs, which show a 2D projection. It has not been investigated whether these methods require any adjustments in order to apply them to stage third molars on magnetic resonance imaging (MRI), which shows 3D information. Aim: To prospectively study root stage assessment of third molars in age estimation using 3 Tesla MRI and to compare this with panoramic radiographs, in order to provide considerations for converting 2D staging into 3D staging and to determine the decisive root. Subjects and methods: All third molars were evaluated in 52 healthy participants aged 14-26 years using MRI in three planes. Three staging methods were investigated by two observers. In sixteen of the participants, MRI findings were compared with findings on panoramic radiographs. Results: Decisive roots were palatal in upper third molars and distal in lower third molars. Fifty-seven per cent of upper third molars were not assessable on the radiograph, while 96.9% were on MRI. Upper third molars were more difficult to evaluate on radiographs than on MRI (p < .001). Lower third molars were equally assessable on both imaging techniques (93.8% MRI, 98.4% radiograph), with no difference in level of difficulty (p = .375). Inter- and intra-observer agreement for evaluation was higher in MRI than in radiographs. In both imaging techniques lower third molars showed greater inter- and intra-observer agreement compared to upper third molars. MR images in the sagittal plane proved to be essential for staging. Conclusion: In age estimation, 3T MRI of third molars could be valuable. Some considerations are, however, necessary to transfer known staging methods to this 3D technique.